2000
DOI: 10.1002/1097-0282(200012)54:7<578::aid-bip100>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular differences in the formation and structure of fine-stranded and particulate β-lactoglobulin gels

Abstract: In order to reveal at a molecular level differences between fine‐stranded and particulate gels, we present an Fourier transform infrared spectroscopic study of the thermal behavior of β‐lactoglobulin (β‐lg) in salt‐free D2O solutions and low ionic strength at different pDs. Differences are found in the denaturation mechanism, in the unfolded state of the protein, in the aggregate formation, and in the strength of the intermolecular interactions. For fine‐stranded gels (pD 2.8 and 7.8), heating induces the diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
191
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(206 citation statements)
references
References 33 publications
13
191
0
2
Order By: Relevance
“…This analysis relative to hemoglobin in bidistilled water aqueous solution revealed a significant increase in b-sheet bands after 4 h of exposure, indicated with arrows in Figure 2, comparing exposed and unexposed spectra. These features can be attributed to the formation of aggregates [20][21][22] .…”
Section: Resultsmentioning
confidence: 99%
“…This analysis relative to hemoglobin in bidistilled water aqueous solution revealed a significant increase in b-sheet bands after 4 h of exposure, indicated with arrows in Figure 2, comparing exposed and unexposed spectra. These features can be attributed to the formation of aggregates [20][21][22] .…”
Section: Resultsmentioning
confidence: 99%
“…To investigate it further, we used the program CD Pro to analyze the secondary structure content by comparison with 50 reference proteins, including 37 soluble proteins and 13 membrane proteins; the calculation showed that our peptide has a high content of ␤-strand and turn at 36.5% and 38.7%, respectively, strongly supporting the experimental data. To validate the CD data further, we used FTIR spectroscopy (13)(14)(15)(16) to determine the secondary structure of the peptide. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the fibril formation, an increased amount of intermolecular b-sheets was detected with Fourier transform infrared spectroscopy; these b-sheets may bind the monomers together in the fibril. 14,15 Dynamic light scattering showed that after short heating times, the fibrils disintegrate during cooling, but after longer heating times, the fibrils do not disintegrate upon cooling. 13 For the industrial application of fibrils in food products, an acceleration of the fibril formation would be advantageous.…”
Section: Introductionmentioning
confidence: 99%